2018
DOI: 10.1245/s10434-018-6551-1
|View full text |Cite
|
Sign up to set email alerts
|

Development and External Validation of a Simplified Nomogram Predicting Individual Survival After R0 Resection for Gastric Cancer: An International, Multicenter Study

Abstract: The novel simplified nomogram simplifies the assessment of individual survival after R0 resection for GC without sacrificing predictive ability. It also has potential for use with other databases and for clinical applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 22 publications
0
22
2
Order By: Relevance
“…Adjuvant chemotherapy: according to the patient's wishes and their physical condition, fluoride-based adjuvant chemotherapy was recommended for most patients with pathological stage II and III disease [20] in our center, as previously described [21,22]. A total of 256 patients (63.8%) received adjuvant chemotherapy, with the median number of cycles being 5 (range 1-12), similar to a previous study [23].…”
Section: Definitionsmentioning
confidence: 65%
“…Adjuvant chemotherapy: according to the patient's wishes and their physical condition, fluoride-based adjuvant chemotherapy was recommended for most patients with pathological stage II and III disease [20] in our center, as previously described [21,22]. A total of 256 patients (63.8%) received adjuvant chemotherapy, with the median number of cycles being 5 (range 1-12), similar to a previous study [23].…”
Section: Definitionsmentioning
confidence: 65%
“…A nomogram is a graphical calculation or algorithm that combines several continuous variables to predict a specific end point using traditional statistical methods (for example, Logistic or Cox regression model) (Kattan, 2002). It has been constructed and verified in a variety of cancers to help clinicians quickly and accurately judge the prognosis of patients (He et al, 2018;Kim et al, 2018;Zheng et al, 2018). Many studies (Bunduc et al, 2018;Kang et al, 2017;He et al, 2013;Ntala et al, 2018;Ansari et al, 2019;Beeghly-Fadiel et al, 2016;Eguchi et al, 2016) have confirmed that the clinical characteristics and prognosis of young patients with PC are different from older patients, but the nomogram of PC in previous studies (He et al, 2018;Song, Miao & Chen, 2018;Li & Liu, 2019) cannot accurately predict the prognosis of young patients with PC.…”
Section: Introductionmentioning
confidence: 99%
“…Both models of Kattan et al10 and Kim et al 38 were developed from Western centers; in the SEER cohort, the AUC of these two models were not significantly different with that of our ANN model (Table 2). However, our ANN model was superior to the models developed from Eastern centers including the model by Zheng et al 39 from China and the models by Han et al, 40 Song et al, 17 and Woo et al 9 from Korea. In the CIAH cohort, the Western models did not perform as well as our ANN model.…”
Section: Resultsmentioning
confidence: 56%
“…After reviewing previous published articles, five nomograms and one scoring model were identified as available for all the three cohorts 9,10,17,38‐40 . Referring to the involved variables for these six models, comparisons among the six models and our ANN model were performed in 3613 patients of the SEER cohort, 2676 patients of the CIAH cohort, and all patients of the PUCHI cohort.…”
Section: Resultsmentioning
confidence: 99%